Directionally Controlled Growth of Fe-Anchored Carbon Fibers by the Electrospinning Process. (27th September 2021) - Vignesh, V.; Nirmala, R.; Srinivasan, M.; Ramasamy, P.; R., Navamathavan; Kim, Hak Yong
Abstract : The utility fit, structurally controlled development of down-scaled products is a great boon to new upcoming device functions for various applications. Fe nanoparticle decorated carbon fibers created through electrospinning offer advancement opportunities due to their capacity for tunable porosity with a high surface to the volume aspect ratio, which enables efficient accessibility, resulting in better performance in device applications. Here, we report on the synthesis of Fe nanoparticle anchored polymer (PVA) fibers created using an electrospinning process followed by a carbonization process was performed at different temperatures of 500 °C, 600 °C, and 700 °C under an inert (Ar) atmosphere. An annealing process allows the formation of pristine Fe ions rather than oxide formation, and the polymer transforms into graphitate by abnormal decomposition in PVA, without changing its fibrous morphology. The fibrous structure with uniform distribution of Fe nanoparticles product was confirmed by scanning electron microscopy, field-effect scanning electron microscopy, scanning tunneling electron microscopy, and tunneling electron microscopy images.